Medical anthropology: description of a curriculum review (Revista Venezolana de Salud Pública, 2018)
The present work reconstructs the experience of the educational process happened during the reform of the program of Medical Anthropology, subject of the ninth semester of the career of medicine of the Deanery of Sciences of the Health of the University Centroccidental Lisandro Alvarado. For it there was realized a documentary review of the programs of the subject between 1998 and 2010, them establishing points of coincidence and the innovations, which used as input for the reformulation of the program. The intention of these changes approved in May, 2014 was orientated towards the revaluation of the social sciences in the study of the career of medicine, under the premise of which the study of the process health - disease involves a series of sociocultural aspects, product of the relation of the individual with the political, social and economic context that surrounds it. The work describes the experience of the educational process that gave origin to the in force program in the frame of the process of reform curricular that is carried out in the university, in order to extract lessons and important experiences that enrich the exercise of the teaching.
Keywords: Social sciences; Education; Curriculum